Patient‐reported outcome measures in nonmelanoma skin cancer of the face: a systematic review. (5th June 2013) - Bates, A.S.; Davis, C.R.; Takwale, A.; Knepil, G.J.
Abstract : What's already known about this topic? The Department of Health supports the use of patient‐reported outcome measures (PROMs) in four common elective surgical procedures (varicose vein surgery, hip and knee arthroplasty and hernia repair). Nonmelanoma skin cancer (NMSC) is the most common malignancy in the U.K. A variety of scales measure patient‐reported outcomes in NMSC. However, no international guidelines exist to direct professionals to a preferred NMSC patient‐completed outcome questionnaire for NMSC. What does this study add? Deficiencies exist within current NMSC questionnaires. Future directions are proposed in order to create a validated PROM for NMSC of the face. See also the Commentary by Black Summary: Nonmelanoma skin cancer (NMSC) is the most common malignancy in the western world, with an incidence of 98 000 in the U.K. Since 2009 the Department of Health (DoH) has collected patient‐reported outcome measure (PROM) data following four common surgical procedures. However, a DoH PROM for NMSC does not exist. A systematic review of questionnaires published on patient concerns due to NMSC of the face was conducted. Keywords relevant to PROMs, NMSC and the facial region were comprehensively searched in medical databases. Inclusion criteria stipulated that questionnaires from relevant papers recruited patients with NMSC for both the item formulation and subsequent validation. Questionnaires were then discussed by a multispecialty skin cancer research team. Initially 2548 papers were found; after exclusion criteria were applied, 73 articles were retrieved. Four patient questionnaires for NMSC featured adequate development and validation according to the inclusion criteria. The Facial Skin Cancer Index (FSCI) was the only PROM specific to facial NMSC. Additional questionnaires identified included the Skin Cancer Quality of Life Impact Tool, Skindex, and Dermatology Life Quality Index. There is a scarcity of data relating to NMSC PROMs and appearance concerns. Only one questionnaire – the FSCI – was specific to patients with facial NMSC. We recommend nationally standardized data collection from patients with NMSC in order to create an evidence‐based validated PROM for patients with facial skin cancer.